Caracterização físico-química e capacidade antioxidante do butiá. - Sganzeria, Marla (2010)
The species belonging to the Palmae (Aracaceae) family are distinguished by the natural and economic resource that they represent to human populations as its ecological role in the vegetation. In Rio Grande do Sul there are six genera of native palm trees, among them occurs the palm Butia genus, mainly the species of B. capitata and B. eriospatha, which produce fruits that are consumed as raw or as byproducts same as juice, liqueur and ice cream. The interest in native species and small fruit is growing in recent years due to the benefit that they can provide to human health, due to the action of compounds derived from the secondary metabolism of plants. Thus, this study aimed to characterize the fruits of B. capitata and B. eriosphata species, determining the nutritional composition, the presence of the phytochemical compounds and the antioxidant capacity of the pulp and kernel fractions. In relation to biometry, pindo palm fruits of both species presented a flat shape due to higher measures of diameter compared with measures of length, besides high-yield pulp (70.97% for B. capitata); the peel color of fruits from both species of pindo palms are located within the first quadrant between the shades of red and yellow. The almond fruits composition stand out levels of fiber and carbohydrates, and also the caloric content of 392.18 kcal.100g-1 and 358.03 kcal.100g-1 (B. capitata and B. eriosphata species, respectively), due to high fat content, which is a good indicator for the extraction of oil, that is rich in medium chain fatty acids (C6-C12), achieving 56.48% for the species of B. capitata and 43.70% for the species of B. eriosphata. Among the phytochemical compounds, highlights the concentration of total phenols, 416.73mg GAE.100g-1 and 443.1973mg GAE.100g-1 in almonds of B. capitata and B. eriosphata species, respectively, and the absence of tocopherols in the almonds of the species evaluated. In relation to the fruit pulp, there was strong positive correlation between soluble solids and total sugars for B. capitata specie (0.990), while for the species B. eriosphata the most significant correlation occurred between soluble solids and acidity content (0.994). The total caloric value was equivalent to 53.21 kcal.100g-1 for B. capitata specie and 42.30 kcal.100g-1 for B. eriosphata specie, mainly due to the carbohydrate content. The fiber content in species of B. capitata (1.22%) and B. eriosphata (0.88%) were lower than the values reported for the fruits from other palm species. Through principal component analysis, considering the physical-chemical composition and the antioxidant activity was possible to differentiate these two species of pindo palm. In the phytochemical composition of pindo palm fruit included the concentration of phenols, vitamin C, which correlated with antioxidant capacity, and the carotenoid content.